Data on the volumes of water stored in the reservoirs supplying the Metropolitan Area of Sao Paulo (2003–2015) - Lima, Gabriela Narcizo de; Lombardo, Magda Adelaide [UNESP]; Magaña Rueda, Víctor Orlando (Elsevier, 2018)
The dataset addressed in this article relates to the research article entitled “Urban water supply and the changes in the precipitation patterns in the Metropolitan Area of Sao Paulo – Brazil” (Lima et al., 2018) [1]. The dataset presents the indices of water volumes stored in the reservoirs that supply water to the Metropolitan Area of Sao Paulo (MASP). These indices were calculated based upon data provided by the Basic Sanitation Company of the State of Sao Paulo (SABESP1) as of the year 2003 (SABESP -Basic Sanitation Company of the State of Sao Paulo, 2017) [2]. These data include air temperature, evapotranspiration, total flow and daily withdrawal. However, due to issues related to information protection, SABESP only provides data on six of the eight water-producing systems that supply the MASP with water. Thus, the data available on the SABESP website each day were collected, processed and entered into this article calculation tables.